Hoya nuttiana (Apocynaceae, Asclepiadoideae), a new species from Sarawak, Malaysian Borneo - Rodda, Michele; Simonsson Juhonewe, Nadhanielle (Phytotaxa, 2013)
A new species, Hoya nuttiana Rodda & Simonsson, endemic of Sarawak, Malaysia is described and illustrated. George Derby Haviland and Charles Hose first collected the species in Sarawak in 1894. More recent collections were made in 1987 and 2007. Hoya nuttiana can be separated from all published Hoya species because it is the only known species with globular inflorescences of up to 100 flowers with campanulate corollas bearing a stalked gynostegium.